2003
DOI: 10.1016/s0741-5214(03)00551-2
|View full text |Cite
|
Sign up to set email alerts
|

Selective management of abdominal aortic aneurysms smaller than 5.0 cm in a prospective sizing program with gender-specific analysis

Abstract: The study confirms the results of the United Kingdom Small Aneurysm Trial and the Aneurysm Detection and Management Study, that is, that risk for rupture is extremely unlikely with AAA smaller than 5.0 cm, which enables safe follow-up surveillance programs in both men and women with AAA smaller than 5.0 cm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
52
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 6 publications
2
52
1
3
Order By: Relevance
“…The publication dates of the 15 potentially eligible studies 13,22,[29][30][31][32][33][34][35][36][37][38][39][40][41] ranged from 1994 to 2009, with patient recruitment from 1976 to 2005. Of these, 10 were prospective studies 13,22,[34][35][36][37][38][39][40][41] (including three randomised trials), four included both retrospective and prospective data 29,30,32,33 and one study reported only retrospective data.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…The publication dates of the 15 potentially eligible studies 13,22,[29][30][31][32][33][34][35][36][37][38][39][40][41] ranged from 1994 to 2009, with patient recruitment from 1976 to 2005. Of these, 10 were prospective studies 13,22,[34][35][36][37][38][39][40][41] (including three randomised trials), four included both retrospective and prospective data 29,30,32,33 and one study reported only retrospective data.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Of these, 10 were prospective studies 13,22,[34][35][36][37][38][39][40][41] (including three randomised trials), four included both retrospective and prospective data 29,30,32,33 and one study reported only retrospective data. 31 Aneurysm growth was the primary outcome measure in 10 of the 15 studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations